2020
DOI: 10.48550/arxiv.2009.05721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-Term and Long-Term Context Aggregation Network for Video Inpainting

Abstract: Video inpainting aims to restore missing regions of a video and has many applications such as video editing and object removal. However, existing methods either suffer from inaccurate short-term context aggregation or rarely explore long-term frame information. In this work, we present a novel context aggregation network to effectively exploit both short-term and long-term frame information for video inpainting. In the encoding stage, we propose boundary-aware shortterm context aggregation, which aligns and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To hallucinate flow inside the masked region, non-learning approaches [22,7] rely on energy minimization assuming smoothness of the flow; [29,5] is a deep learning solution that first computes flow between image pairs, then uses a neural network to hallucinate flow inside the masked region. End-to-end learning methods [11,26,19,38,2,37,15] model cross-frame correspondence in their loss functions. For example, [38] jointly infers appearance and flow while penalizing temporal inconsistency.…”
Section: Related Workmentioning
confidence: 99%
“…To hallucinate flow inside the masked region, non-learning approaches [22,7] rely on energy minimization assuming smoothness of the flow; [29,5] is a deep learning solution that first computes flow between image pairs, then uses a neural network to hallucinate flow inside the masked region. End-to-end learning methods [11,26,19,38,2,37,15] model cross-frame correspondence in their loss functions. For example, [38] jointly infers appearance and flow while penalizing temporal inconsistency.…”
Section: Related Workmentioning
confidence: 99%
“…These techniques concentrate on repairing single-frame images and wonderful results have been achieved. Some recent research results [10][11][12], in particular, have shown that deep learning methods have excellent repair capabilities. Furthermore, video repair and related technologies can also be used for tasks such as eliminating watermarks [13], object removal [14], and movie special effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques concentrate on repairing single-frame images and wonderful results have been achieved. Some recent research results [10][11][12], in particular, have shown that deep learning methods have excellent repair capabilities. Furthermore, video repair and related technologies can also be used for tasks such as eliminating watermarks [13], object removal [14], and movie special effects [15].…”
Section: Introductionmentioning
confidence: 99%